The association between a body shape index and elevated urinary albumin–creatinine ratio in Chinese community adults - Zhang, Yue; Gao, Wenxing; Li, Binqi; Liu, Yang; Chen, Kang; Wang, Anping; Tang, Xulei; Yan, Li; Luo, Zuojie; Qin, Guijun; Chen, Lulu; Wan, Qin; et al. (Frontiers in Endocrinology, 2022)
Abstract Background: Obesity, especially visceral obesity, seems to be one of the most decisive risk factors for chronic kidney disease. A Body Shape Index (ABSI) is an emerging body size measurement marker of visceral obesity. This study aimed to explore whether ABSI links with albuminuria in Chinese community adults. Methods: This cross-sectional study enrolled 40,726 participants aged 40 or older from seven provinces across China through a cluster random sampling method. ABSI was calculated by body mass index, waist circumference, and height. Increased albuminuria was defined as Urinary albumin-creatinine ratio (UACR)≥30mg/g, indicating kidney injury. For ABSI, we divided it by quartile cutoff points and tried to determine the association between ABSI levels and UACR by multiple regression analysis. DAG(Directed Acyclic Graph) was plotted using literature and expert consensus to identify potential confounding factors. Results: The average age of subjects with elevated UACR was 61.43±10.07, and 26% were men. The average age of subjects with normal UACR was 57.70±9.02, and 30.5% were men. Multiple logistic regression analysis was conducted and demonstrated that the ABSI quartiles were related to elevated UACR positively(OR[95%CI]Q2 vs. Q1: 1.094[1.004,1.197]; OR[95%CI]Q3 vs. Q1: 1.126[1.030,1.231]; OR[95%CI]Q4 vs. Q1: 1.183[1.080,1.295], P for trend<0.001) after adjustments for confounding factors. The stratified analysis further showed that with the mounting for ABSI levels, elevated UACR more easily occurred in the people characterized by the elderly, men, and hypertension. Conclusions: In Chinese community adults, people with higher ABSI levels can be deemed as the high-risk individuals with UACR elevation, and it will be beneficial for them to lose weight and significantly reduce visceral fat.